2021
DOI: 10.3389/fmicb.2021.702951
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Restrictive Medium for Monascus Enrichment From Hongqu Based on the Synergistic Stress of Lactic Acid and Ethanol

Abstract: Graphical AbstractThe restrictive medium containing lactic acid and ethanol enabled the enrichment of Monascus sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Saccharomyces became one of the dominant fungi on the 7th day of fermentation, and then dominated the subsequent fermentation process. Previous study had shown that Monascus has excellent ability to produce liquefaction and and saccharifying enzymes ( Zhou et al, 2021 ). In this study, high-throughput sequencing results showed that Monascus has a relatively higher abundance in HBAW fermentation than LBAW, so the reducing sugar content in HBAW was obviously higher than that of LBAW at the early stage of fermentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharomyces became one of the dominant fungi on the 7th day of fermentation, and then dominated the subsequent fermentation process. Previous study had shown that Monascus has excellent ability to produce liquefaction and and saccharifying enzymes ( Zhou et al, 2021 ). In this study, high-throughput sequencing results showed that Monascus has a relatively higher abundance in HBAW fermentation than LBAW, so the reducing sugar content in HBAW was obviously higher than that of LBAW at the early stage of fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…As a typical representative of Chinese rice wine, Hongqu rice wine possesses bright red color, subtle sweet taste, typical mellow flavor and health functions due to the addition of Hongqu (red mold rice). As a starter for Hongqu rice wine, Hongqu is made from steamed rice by solid-state fermentation with the inoculation of starter cultures ( Qumu , Monascus as the predominant microbe) ( Liu et al, 2018 ; Zhou et al, 2021 ). Similar to other traditional fermented foods, Hongqu is usually prepared in a non-sterile, open fermentation environment.…”
Section: Introductionmentioning
confidence: 99%
“…The 1.0 g sample was evenly spread on the potato dextrose agar (PDA) medium, and 1 mL of sterilized lactic acid solution (50%) was added to cover the sample. And then they were incubated at 30 • C. Next, the white and red colonies were continuously selected and transferred to the new PDA medium by drawing lines method (Zhou et al, 2021).…”
Section: Directional Screening Of Monascus Via Culture-dependent Methodsmentioning
confidence: 99%
“…And then they were incubated at 30°C. Next, the white and red colonies were continuously selected and transferred to the new PDA medium by drawing lines method ( Zhou et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation